"We have to learn how to balance all of that": Community health needs of a state-recognized Gulf Coast Indigenous tribe. Issue 4 (2nd October 2022) - Liddell, Jessica L.; Carlson, Tess; Beech, Haley H.
ABSTRACT: The community and health programmatic needs of state-recognized tribes vary in comparison to tribes who are federally recognized. Federal recognition provides tribes with access to federal programs through Indian Health Services (IHS) and ensures a certain level of sovereignty. Little research explores the gaps in community programs experienced by state-recognized tribes as a result of their non-federal status or explores their resilience as a community in filling these gaps through other supports. Through collaboration with a community advisory board (CAB), a qualitative descriptive methodology was used to conduct 31 semi-structured interviews with adult women that self-identify as members of a state-recognized Gulf Coast Indigenous tribe. Using conventional content analysis, the following themes were identified: (a) Wellness Programs and the Power of Connection (b) Transmission of Traditional Knowledge (c) The Need for Women's Support Groups; (d) Gaps in Programs; and (e) Barriers to Participating in Community and Tribal Programs. These results demonstrate the immense importance of community events as opportunities for transmission of cultural knowledge for tribal members, an integral aspect of securing tribal holistic wellbeing. Although social support and enculturation activities contribute to Indigenous groups' overall health, this topic has been less studied for state-recognized tribes, particularly for those in the Gulf Coast tribe. Key implications of this study include the need for federal recognition and increased access to programmatic resources and highlights the importance of increased support and sovereignty for state-recognized tribes.